"Sistema de gestión administrativa-Operativa y su incidencia en la producción y rentabilidad de Reybanpac C.A. periodo 2013-2014, Plan administrativo de gestión". - Moreira Duarte, Gabriela Liseth (2015)
One of the most important roles and responsibilities of managers and business managers is the efficient and effective management of resources, they must ensure that the administrative and operational processes are met through strategies and / or management tools to turn your weaknesses into strengths and threats into opportunities, resulting in administrative and operational management according to the requirements of the environment. The general objective pursued research to assess the impact of the administrative management system - Operational in banana production and profitability of the company Reybanpac. It is defined as a research field explanatory and descriptive, qualitative in nature where processes and activities and quantitative calculations based on the respective management indicators are addressed. The collection of information was obtained by interviewing application with the production manager and administrative staff surveys to determine how activities are run and get data resulting from the management and production records were also reviewed historical information operational and financial periods under study. With the information obtained analysis results, the product of the responses of employees who were selected as a sample, to determine the incidence of administrative and operational management on profitability and business productivity Reybanpac in study.